Genre organization in specialized discourse: Disciplinary variation across university textbooks. (February 2014) - Parodi, Giovanni
Not many studies have focused on the analysis of the rhetorical organization of a genre and the respective frequency of occurrence of moves and steps as they occur in a corpus across disciplines – particularly, with a complementary qualitative-quantitative approach. This article aims to become a step in helping to fill this gap in research on Spanish. In this way, the textbook genre, the occurrence of its rhetorical macro-moves, moves and steps and disciplinarity are the central focus of this study. More specifically, in this article we seek to determine and to compare the frequency of occurrence of macro-moves, moves and steps in a corpus of 126 university textbooks across the academic discourse of four disciplines. We distinguish the major areas of knowledge (Basic Sciences and Engineering and Social Sciences and Humanities) as well as the specific disciplines (Social Work, Psychology, Industrial Chemistry and Construction Engineering). The main findings show there are differences between the occurrence of some discourse moves and steps across the texts of disciplines under study, which reveals a distinctive feature in the didactic component of textbooks. So we can infer that knowledge construction process through this genre is not carried out in the same way and that disciplinarity plays an important role in the diversifying organizational discourse patterns detected.